Association between periconceptional weight loss and maternal and neonatal outcomes in obese infertile women - van Oers, Anne M. (PLoS One, 2018)
BACKGROUND: Obesity in women of reproductive age has deleterious effects on reproductive and offspring health. In this study, we aimed to evaluate the association between the magnitude of periconceptional body-mass index (BMI) change and maternal and neonatal outcomes in obese infertile women who participated in the LIFEstyle study. The LIFEstyle study was a randomized controlled trial, evaluating if a six-month lifestyle intervention program prior to infertility treatment in obese infertile women improved birth rates, compared to prompt infertility treatment. METHODS AND FINDINGS: This is an exploratory post hoc analysis of the LIFEstyle study. We recorded periconceptional BMI change in women with an ongoing pregnancy, pooling data of all women, regardless of randomization arm. Periconceptional BMI change was calculated using weight at randomization and the periconceptional weight (measured in kilograms 12 weeks before or after conception and expressed as BMI change in units BMI (kg/m(2))). Subsequently, women were categorized into quartiles according to the magnitude of their periconceptional change in BMI. The odds of maternal and neonatal outcomes were calculated using logistic regression analysis, comparing women in each of the first three weight change quartiles separately, and combined, to women in the fourth quartile. The fourth quartile was chosen as reference group, since these women had the least weight loss. We adjusted for periconceptional BMI, nulliparity and smoking status. In addition, we performed a subgroup analysis for singleton pregnancies. In the LIFEstyle study, 321 obese infertile women achieved an ongoing pregnancy which was conceived within 24 months after randomization. Periconceptional BMI change was available in 244 of these women (76%). Median BMI at randomization was 35.9 kg/m(2). Women in the first quartile (Q1) had a periconceptional BMI change of <-2.1 kg/m(2), women in the second quartile (Q2) -2.1 to -0.9 kg/m(2), women in the third quartile (Q3) -0.9 to 0.1 kg/m(2) and women in the fourth quartile (Q4) gained ≥0.1 kg/m(2). There were no significant differences between women in the quartiles regarding rates of excessive gestational weight gain (in term pregnancies), gestational diabetes, preterm birth, induction of labor, spontaneous vaginal birth and Caesarean section. Compared to women in Q4, the adjusted odds ratios, aOR, and 95% confidence interval for a hypertensive complication were; 0.55 (0.22–1.42) for women in Q1, 0.30 (0.12–0.78) for women in Q2, 0.39 (0.16–0.96) for women in Q3 and 0.39 (0.19–0.82) for women in Q1 to Q3 combined. In the subgroup analysis, investigating singleton pregnancies only, the statistically significant decreased rate of a hypertensive complication remained in women in Q2 (aOR 0.27, 95% CI 0.10–0.72) and Q3 (aOR 0.39, 95%CI 0.16–0.98) and when comparing women in Q1 to Q3 together to women in Q4 (aOR 0.38, 95%CI 0.18–0.80). Furthermore, there was a significantly decreased aOR (95%CI) of preterm birth in women in Q2 (0.24, 0.06–0.98) and when combining women in Q1 to Q3 (0.37, 0.14–0.97) compared to women in Q4. CONCLUSIONS: These results suggest that a periconceptional decrease in BMI in obese infertile women could lead to a decrease of the rates of hypertensive pregnancy complications and preterm birth. The results are limited by the exploratory nature of the analyses and further evidence is necessary to provide more definitive conclusions.